2017
DOI: 10.1016/j.pec.2017.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Don’t need help, don’t want help, can’t get help: How patients with brain tumors account for not using rehabilitation, psychosocial and community services

Abstract: ObjectiveTo understand why some adults with primary brain tumors do not use support services despite indications of a need for help. MethodsNineteen adults recently diagnosed with primary brain tumors participated in semi-structured interviews. Thematic analysis was used to identify recurrent ways participants explained their non-use of support services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 49 publications
0
32
0
Order By: Relevance
“…The mental and physical distress would lead to low quality of life, predicate poor therapeutic effect, and satisfaction with health care [ 13 ]. Routine screening and evaluation of distress in brain tumor patients may assist medical workers to develop proper intervention [ 13 , 33 , 34 ], which may improve prognosis [ 35 ]. More studies should be planned to identify the risk factors of brain tumor patients and integrate appropriate interventions to improve HRQoL.…”
Section: Discussionmentioning
confidence: 99%
“…The mental and physical distress would lead to low quality of life, predicate poor therapeutic effect, and satisfaction with health care [ 13 ]. Routine screening and evaluation of distress in brain tumor patients may assist medical workers to develop proper intervention [ 13 , 33 , 34 ], which may improve prognosis [ 35 ]. More studies should be planned to identify the risk factors of brain tumor patients and integrate appropriate interventions to improve HRQoL.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding IECA, we observed an improvement in patients’ assistential network perceived efficacy ( P = .001). To date, there are no literature evidences in BTRE patients population that investigate this aspect; there are only few studies on patients with BT that highlight the importance for them to receive support by social services, but at the same time they indicate the difficulty for them to recognizing which service could support their requests . In our MRP, social worker addressed patients to specific territorial services in case of particular requests related to their condition (financial benefits, special medical devices, driving license for patients with epilepsy, home assistance).…”
Section: Discussionmentioning
confidence: 99%
“…Literature data suggest that quality of survival in this patient population should be as important as the duration of survival itself . This could mean to obtain a good seizure control with no relevant side effects, as well as to give emotional support for patients and their families, and to offer the possibility to receive neuropsychological rehabilitation for cognitive deficits and obtain social assistance for personal needs …”
Section: Introductionmentioning
confidence: 99%
“…The literature on the need for help with social problems among cancer patients is also limited. Previously published studies reported that a relatively low need for help (despite reporting problems) was associated with a preference for self‐managing psychosocial problems and relying on family members and friends . A systematic review of the barriers to the delivery of psychosocial care to cancer patients reported that a patient's perceived barriers included the lack of information, no confidence in services, stigma about psychosocial care, and communication barriers between health‐care providers and patients; however, all of these barriers were reported by North American, Australian, and European studies …”
Section: Introductionmentioning
confidence: 99%
“…Previously published studies reported that a relatively low need for help (despite reporting problems) was associated with a preference for self-managing psychosocial problems and relying on family members and friends. 5,[21][22][23][24][25][26] A systematic review of the barriers to the delivery of psychosocial care to cancer patients reported that a patient's perceived barriers included the lack of information, no confidence in services, stigma about psychosocial care, and communication barriers between health-care providers and patients; however, all of these barriers were reported by North American, Australian, and European studies. 27 The ultimate goals of this research project are to develop an instrument to assess cancer-related social problems, to effectively identify socially distressed patients with cancer of any organ in any disease stage, to investigate acceptable and effective support mechanisms for those patients, and to improve the QOL of cancer outpatients in Japan by using an original instrument to screen for psychosocial distress.…”
Section: Introductionmentioning
confidence: 99%